Influence of Ethylene Signaling in the Crosstalk Between Fe, S, and P Deficiency Responses in Arabidopsis thaliana - García, María José; Angulo, Macarena; García, Carlos; Lucena, Carlos; Alcántara, Esteban; Pérez-Vicente, Rafael; Romera, Francisco Javier (Frontiers in Plant Science, 2021)
To cope with P, S, or Fe deficiency, dicot plants, like Arabidopsis, develop several responses (mainly in their roots) aimed to facilitate the mobilization and uptake of the deficient nutrient. Within these responses are the modification of root morphology, an increased number of transporters, augmented synthesis-release of nutrient solubilizing compounds and the enhancement of some enzymatic activities, like ferric reductase activity (FRA) or phosphatase activity (PA). Once a nutrient has been acquired in enough quantity, these responses should be switched off to minimize energy costs and toxicity. This implies that they are tightly regulated. Although the responses to each deficiency are induced in a rather specific manner, crosstalk between them is frequent and in such a way that P, S, or Fe deficiency can induce responses related to the other two nutrients. The regulation of the responses is not totally known but some hormones and signaling substances have been involved, either as activators [ethylene (ET), auxin, nitric oxide (NO)], or repressors [cytokinins (CKs)]. The plant hormone ET is involved in the regulation of responses to P, S, or Fe deficiency, and this could partly explain the crosstalk between them. In spite of these crosslinks, it can be hypothesized that, to confer the maximum specificity to the responses of each deficiency, ET should act in conjunction with other signals and/or through different transduction pathways. To study this latter possibility, several responses to P, S, or Fe deficiency have been studied in the Arabidopis wild-type cultivar (WT) Columbia and in some of its ethylene signaling mutants (ctr1, ein2-1, ein3eil1) subjected to the three deficiencies. Results show that key elements of the ET transduction pathway, like CTR1, EIN2, and EIN3/EIL1, can play a role in the crosstalk among nutrient deficiency responses.